Professional development needs, support, and barriers: TALIS US new and veteran teachers' perspectives. Issue 3 (26th May 2020) - Zhang, Shaoan; Shi, Qingmin; Lin, Emily
ABSTRACT: Drawing on 1508 US secondary teachers' data from Teaching and Learning International Survey (TALIS) 2013, this study examines new and veteran US teachers' needs, support, and barriers for professional development (PD). The results indicated that both veteran and new teachers reported needing PD that addresses implementation of national/state curriculum standards or Common Core standards and technology, teaching students with special needs, and approaches to individualized learning. A larger proportion of each group also reported that they received neither a salary supplement nor non-monetary support for PD activities. However, more new teachers than veteran teachers reported receiving a salary supplement for PD activities outside working hours; veteran teachers reported more barriers for PD participation due to financial cost and lack of incentives and time outside the school contract. This study provided implications for PD design and implementation in the US context.